Electrochemical determination of Ag-ions in environment waters and their action on plant embryos - Mikelova, Radka; Baloun, Jiri; Petrlova, Jitka; Adam, Vojtech; Havel, Ladislav; Petrek, Jiri; Horna, Ales; Kizek, Rene (Bioelectrochemistry (Amsterdam, Netherlands), 2007)
We utilized liquid chromatography coupled with electrochemical detector (HPLC-ED) for analyzing of silver ions. The optimization of basic chromatographic parameters has been done. The detection limit (3 S/N) obtained were 20 nmol/dm(3). Influence of different interferences (anions and cations) on current response of silver ions has been described. Moreover, we used HPLC-ED to analyze waters of different purity including photographic emulsion, which naturally contained silver ions. We found out that content of silver ions in the emulsion was 1.57 x 0.03 mmol/dm(3). Moreover, we investigated influence of silver ions on early somatic embryos of Blue Spruce. We were interested in the issue how much silver ions can embryos uptake during four days long treatment. For this purpose, we used optimized HPLC-ED technique. The content increased with increasing treatment time and applied concentration. We also studied how silver ions can influence thiols content in the treated embryos. For these purposes we used adsorptive transfer stripping voltammetry in connection with differential pulse voltammetry--Brdicka reaction. It clearly follows from the obtained results that content of thiols increased with increasing treatment time and applied concentration.
Keywords: semena rostlinná; monitorování životního prostředí; Electrochemistry; Environmental Monitoring; Water Pollutants, Chemical; stříbro; Seeds; smrk; Silver; elektrochemie; Picea; chemické látky znečišťující vodu